In-silico therapeutic investigations of arjunic acid and arjungenin as an FXR agonist and validation in 3T3-L1 adipocytes. (February 2020) - T, Mohan Manu; T, Anand; P, Bhuvanesh Kumar; Fathima, Asra; Khanum, Farhath
Graphical abstract: Highlights: Structure-based pharmacophores screening of arjungenin and arjunic acid were predicted potential FXR agonist. In-Silico ADMET studies of arjungenin and arjunic acid identified as non-toxic and has druggable property. Molecular docking studies confirmed arjungenin and arjunic acid as a strong and stable binding towards FXR protein. In-vitro studies with 3T3-L1 adipocytes confirm decreased cyp7a1 levels and increased FXR, PPAR-γ and SREBP-1c levels. Abstract: The present study was to illustrate the agonistic property of arjungenin and arjunic acid towards farnesoid X receptor protein (FXR).The pharmacokinetic properties like molecular interactions, absorption, distribution, metabolism, elimination and toxicity (ADMET) of the ligands were checked through in-silico studies. Protein-ligand docking was carried out using autodock software. Molecular docking analysis confirmed strong binding energy and interaction of arjungenin and arjunic acid with the target protein and the ADMET profiles identified for both compounds were promising.Further in vitro studies were performed in 3T3-L1 adipocyte to verify the agonistic property of arjungenin and arjunic acid. Oil red O staining was done to check differentiation induction. Adiponectin, leptin, triglycerides and total cholesterol levels were quantified. The mRNA expression of FXR, Cyp7a1, PPAR-γ and SREBP-1c were quantified using fluorescent real-time PCR. Cytotoxicity assay was confirmed that up to 150 μM concentration there is no significant cell death on treatment with arjunic acid and arjungenin. Treatment with arjungenin and arjunic acid confirms increased differentiation of the cells with significant ( P  < 0.05) increase in adiponectin (118.07% and 132.92%) and leptin (133.52% and 149.74%) protein levels compared to the negative control group. After treatment with arjungenin and arjunic acid in 3T3-L1 preadipocytes the mRNA expression of FXR, PPAR-γ and SREBP-1c were significantly ( P  < 0.01) increased and cyp7a1 was significantly ( P  < 0.01) decreased when compared with the negative control group. Overall, our results suggest that arjungenin and arjunic acid acts as an FXR agonist and may be useful for rational therapeutic strategies as a novel drug to treat cholesterol mediated metabolic syndrome and insulin resistance.